The Relationship Between Language, Culture, and Student Identity : Penelitian - Febriani; Hamzah; Andi Islah Hanief Padmanegara; Azisah Nurul Ilmi Andi Kasymir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Language plays a strategic role in shaping individual identity, particularly within the context of higher education. The use of english in universities functions not only as a medium of academic communication but also as a significant factor influencing students’ cultural and academic identity contruction. This study aims to examine the relationship between language, culture, and student udentity at universitas muhammadiyah bone, with a specific focus on english language practices. Employing a qualitative approach with a narrative analysis design, data were collected through in depth interviews with eight students who actively use english in academic settings. The findings reveal that english contributes to the formation of the students’ academic identities as globally oriented individuals, enhances academis self confidences, and serves as a spce for negotiating local identity, islamic values, and global academic demands. This study recommens that english language instruction in higher education be oriented toward fostering cultural awareness and strengthening student identity.